2021
DOI: 10.3390/scipharm90010004
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uses, Phytochemistry, and Pharmacology of Elegia Species: A Review

Abstract: In South Africa, plants belonging to the Restionaceae family possess an ecological dominance. As a result, they have been the subject of numerous morphological, anatomical, and evolutionary studies. However, few studies have focused on their phytochemical profile and their potential pharmacological activities. The genus Elegia L. is the second largest of this family comprising 52 species, which are mainly used as materials for thatching. Limited studies on the chemical constituents of Elegia species and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Benito-Román et al showed that red onion skin waste contains more myricetin than that of yellow onions [ 6 ], as was the case in our results, although the difference in content was not as distinct. Laricitrin, a 3′-MeO analog of myricetin [ 40 ], is a less common flavonol that has not been thoroughly studied as compared to kaempferol or quercetin [ 41 ]. It was reported that laricitrin could suppress certain factors and decrease the progression of lung cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benito-Román et al showed that red onion skin waste contains more myricetin than that of yellow onions [ 6 ], as was the case in our results, although the difference in content was not as distinct. Laricitrin, a 3′-MeO analog of myricetin [ 40 ], is a less common flavonol that has not been thoroughly studied as compared to kaempferol or quercetin [ 41 ]. It was reported that laricitrin could suppress certain factors and decrease the progression of lung cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%